2014 outbreak of enterovirus D68 in North America. Issue 5 (4th November 2015) - Messacar, Kevin; Abzug, Mark J.; Dominguez, Samuel R.
Abstract : Enterovirus D68 (EV‐D68) is an emerging picornavirus which causes severe respiratory disease, predominantly in children. In 2014, the largest and most widespread outbreak of EV‐D68 described to date was reported in North America. Hospitals throughout the United States and Canada reported surges in patient volumes and resource utilization from August to October, 2014. In the US a total of 1, 153 infections were confirmed in 49 states, although this is an underestimate of the likely millions of cases that occurred but were not tested. EV‐D68 was detected in 14 patients who died; the role of the virus in these deaths is unknown. A possible association between EV‐D68 and cases of acute flaccid paralysis with spinal cord gray matter lesions, known as acute flaccid myelitis, was observed during the outbreak and is under investigation. The 2014 outbreak of EV‐D68 in North America demonstrates the public health importance of this emerging pathogen. J. Med. Virol. 88:739–745, 2016 . © 2015 Wiley Periodicals, Inc.